Kradzieże samochodów w Polsce jako element ryzyka w ubezpieczeniach auto casco - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2015)
The problem of car theft has been observed for many years. The largest scale ofthis phenomenon occurred in the 1990’s. In this paper, the issue is discussed insocial, ethical and economic aspects. We present the scale of the phenomenon ofthe theft of passenger vehicles in Poland in the years 2001–2012 in terms of thenumber of vehicles, type of stolen vehicles and the accident areas. In addition, wepresent the cause of theft and selected ways to protect cars from it. We also brieflydiscuss the role and responsibility of the insurance companies.